Speed breeding in maize (Zea mays) vis-à -vis in other crops: Status and prospects - SINGH, ISHWAR; SHEORAN, SEEMA; KUMAR, BHUPENDER; KUMAR, KRISHAN; RAKSHIT, SUJAY (The Indian Journal of Agricultural Sciences, 2021)
The prevailing global climate change and population explosion have threatened global food security by mounting the demand of more quantity and better quality food. Crop breeding attempts to meet this increasing demand but having a major limitation of long breeding cycle required for developing any suitable cultivar. Therefore, shortening the crop duration in every generation of a breeding cycle has been a long dream of breeders. In the past, many efforts have been made to fasten crop generation time by implementing several techniques like shuttle breeding, embryo rescue, and doubled haploid. In this direction, recently, speed breeding (SB) has emerged as a novel technology to shorten the crop breeding cycle and fasten the crop improvement through rapid generation advancement. Growing crops in the customized growth chambers of SB helps to speed up research on crops with adult plant phenotyping, crossing, mutant studies, and transformation. Till now many crop-specific protocols have been developed in wheat, rice, barley, canola, etc. for SB in growth chambers or glasshouses with controlled environmental conditions. But, still, SB protocol for maize (Zea mays L.), one of the three major staple foods worldwide has not been developed yet. Considering the multiple uses and economic importance of maize, there is a need to accelerate its production to meet future demands. Deploying the SB technique in maize could be beneficial in achieving the same. Thus, despite being challenging, we need to explore the possibilities of using SB in the maize breeding programme. The present review throws light on the current status of SB and future perspectives to make SB successful in maize. The adoption of SB along with other breeding methodologies can be an effective and efficient tool to develop suitable maize hybrids in a short time frame for meeting global demands.